Determination of light elements using the RBS method - Kokkoris, M.; Zarkadas, Ch.; Harissopulos, S.; Kossionides, E.; Paradellis, T. (HNPS Advances in Nuclear Physics, 2020)
The RBS (Rutherford Backscattering Spectroscopy) method is a classical method which has been successfully used for the study and analysis of surface elements. The strong points as well as the weaknesses of the technique are briefly outlined and emphasis is given in the determination of light elements. A method is proposed in order to overcome the problem and the first results and prospects for the future are analysed.